Can needle nitrogen content explain the interspecific difference in ozone sensitivities of photosynthesis between Japanese larch (Larix kaempferi) and Sakhalin fir (Abies sachalinensis)? - Sugai, T; Kitao, M; Watanabe, T; Koike, T (Photosynthetica)
Although deciduous and evergreen conifers are expected to utilize needle nitrogen differently, their interspecific differences in the ozone sensitivity remain unclear. We compared the growth and physiological responses to elevated O3 concentrations in deciduous Japanese larch (Larix kaempferi) and evergreen Sakhalin fir (Abies sachalinensis) seedlings. Seedlings of both species were exposed to 62.5 ± 1.95 nmol(O3) mol-1 during the day time in open-top chambers. Elevated O3 had no effect on height or diameter growth in either of the species but suppressed photosynthetic parameters. A decline in photosynthetic nitrogen-use efficiency was observed in both species. However, needle N content in larch was decreased by O3, whereas it was not decreased in fir. Needle N responses to O3 were different between larch and fir seedlings, indicating that the O3 sensitivity of photosynthesis could vary depending on needle N dynamics. We also observed a higher correlation between photosynthesis and needle N even under O3 exposure, particularly in the mass-based relationship with higher accuracy. The result indicated that mass-based needle N could explain difference in O3 sensitivity of photosynthesis between the different leaf habits in larch and fir seedlings. T. Sugai, M. Kitao, T. Watanabe and T. Koike. Obsahuje bibliografické odkazy